Effects of deep tillage combined with organic amendments application on carbon and nitrogen storage within aggregates and wheat yield - Cheng, Wenlong; Bu, Rongyan; Han, Shang; Tang, Shan; Wang, Hui; Li, Min; Zhu, Rui; Jiang, Fahui; Tang, Mengmeng; Wu, Ji (Frontiers in Plant Science, 2025)
IntroductionSoil organic carbon (SOC) and total nitrogen (TN) stocks are key determinants of the productive capacity of agricultural soils. This study aims to elucidate the effects of long-term tillage practices combined with organic amendments on SOC and TN sequestration within soil aggregates and their subsequent relationship with wheat yield.MethodsA six-year field experiment (initiated in 2016) was conducted, evaluating the following treatments: rotary tillage with straw, rotary tillage with manure, rotary tillage with straw plus manure, deep tillage with straw, deep tillage with manure and deep tillage with straw plus manure.ResultsRelative single organic amendments, both rotary and deep tillage with straw plus manure significantly enhanced macro-aggregate-associated SOC and TN stocks in the 0–15 cm layer by 7.86–23.29% and 16.36–18.99%, respectively. In the 15–30 cm layer, deep tillage with single organic amendments increased macro-aggregate-associated SOC and TN contents by 7.56–18.81% and 5.29–21.47%, respectively compared with rotary tillage. However, deep tillage also reduced macro-aggregate proportions by 5.36–8.16%, which decreased associated SOC and TN stocks by 6.12–7.87% and 6.99–8.53%, respectively. In contrast, deep tillage with straw plus manure increased macro-aggregate-associated SOC and TN contents (18.42–19.39% and 10.17–12.76%, respectively) without reducing macro-aggregate proportions, thereby enhancing SOC and TN stocks in macro-aggregates by 10.49–26.89% and 9.07–26.32%, respectively.DiscussionThese findings indicate that the enrichment of subsoil macro-aggregate-associated SOC and TN strongly correlated with higher wheat yield, demonstrating that deep tillage with straw and manure is an effective practice for improving soil health and sustaining productivity.